2011
DOI: 10.1111/j.1754-9434.2011.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Debate on the Uniform Guidelines and the Disparate Impact Theory of Discrimination

Abstract: This response summarizes commentaries on the M. A. McDaniel, S. Kepes, and G. C. Banks (2011) article, which argued that the Uniform Guidelines on Employee Selection Procedures are a detriment to the field of personnel selection. Several themes were present in the commentaries. No compelling arguments were presented to dispute the assertion that mean racial differences in job-related attributes will be with us for a long time. However, compelling arguments were made that the disparate impact theory of discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Barrett et al (2011) proposed the vague recommendation that "researchers should collaborate and engage in a professional discussion of ethnic group differences in test scores" (p. 535). And as McDaniel et al (2011a) observed, the courts are unlikely to change their practices without fundamental changes to the Civil Rights Act of 1991. Yet, these authors other than seeking to "foster constructive debate" (2011a, p. 570), admit "no substantive experience in how to resolve the unfortunate situation with the Uniform Guidelines" (2011b, p. 509).…”
Section: G Camillimentioning
confidence: 83%
See 4 more Smart Citations
“…Barrett et al (2011) proposed the vague recommendation that "researchers should collaborate and engage in a professional discussion of ethnic group differences in test scores" (p. 535). And as McDaniel et al (2011a) observed, the courts are unlikely to change their practices without fundamental changes to the Civil Rights Act of 1991. Yet, these authors other than seeking to "foster constructive debate" (2011a, p. 570), admit "no substantive experience in how to resolve the unfortunate situation with the Uniform Guidelines" (2011b, p. 509).…”
Section: G Camillimentioning
confidence: 83%
“…First, they argued that both the constructs and methods of measurement must be similar for VG to apply to a local test, and "Though the Principles address VG, they do not support its cavalier use" (p. 548). Second, they noted that while McDaniel et al (2011a) provided evidence of group differences on many important selection variables, one was notably absent from their list: job performance. This is important to consider because the Black versus White gap in performance is considerably smaller than many other predictors of job success.…”
Section: G Camillimentioning
confidence: 96%
See 3 more Smart Citations